2020
DOI: 10.3390/cells9071596
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Therapeutic Targets to Reverse or Prevent the Transition from Metabolically Healthy to Unhealthy Obesity

Abstract: The prevalence of obesity and obesity-related metabolic comorbidities are rapidly increasing worldwide, placing a huge economic burden on health systems. Excessive nutrient supply combined with reduced physical exercise results in positive energy balance that promotes adipose tissue expansion. However, the metabolic response and pattern of fat accumulation is variable, depending on the individual’s genetic and acquired susceptibility factors. Some develop metabolically healthy obesity (MHO) and are resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 186 publications
(255 reference statements)
0
18
1
Order By: Relevance
“…Apart from genetic predisposition, poor dietary habits (eg, increase total fat intake), less physical activity, disrupted circadian rhythm, and psychological unhealthy have also considered taking charge of this metabolic shift, which provide us the intervention targets for lifestyle and medical therapy. 32,33 Although we did not confirm the relationship between diet or exercise and the transition probability from MHO to MUO, other studies found that lifestyle interventions significantly improve metabolic conditions without weight loss, partly due to their anti-inflammation function. Polyphenols, which have been found beneficial for cardiovascular risk factors in T2D patients (the TOSCA.IT study), 34 could also extend the lifespan with improved plasma lipid levels and endotoxemia and decreased immune cell infiltration to the adipose tissue in obese mice, which was independent of body weight.…”
Section: Discussioncontrasting
confidence: 77%
“…Apart from genetic predisposition, poor dietary habits (eg, increase total fat intake), less physical activity, disrupted circadian rhythm, and psychological unhealthy have also considered taking charge of this metabolic shift, which provide us the intervention targets for lifestyle and medical therapy. 32,33 Although we did not confirm the relationship between diet or exercise and the transition probability from MHO to MUO, other studies found that lifestyle interventions significantly improve metabolic conditions without weight loss, partly due to their anti-inflammation function. Polyphenols, which have been found beneficial for cardiovascular risk factors in T2D patients (the TOSCA.IT study), 34 could also extend the lifespan with improved plasma lipid levels and endotoxemia and decreased immune cell infiltration to the adipose tissue in obese mice, which was independent of body weight.…”
Section: Discussioncontrasting
confidence: 77%
“…Adipogenesis, as defined by the formation of adipocytes from stem cells [1], and the adipose tissue itself have drawn much attention at the onset of chronic inflammation in metabolic diseases, such as type 2 diabetes mellitus, cardiovascular diseases, and in several types of cancer [2,3]. Among the processes involved in the setting of these diseases, the adipose tissue secretome has been inferred to play a crucial paracrine regulatory role in brain cancer [4], prostate cancer [5], bladder cancer [6], breast cancer [7], and colon cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing investigations into the biological functions of LDs have revealed that LDs are not just inert intracellular storage depots of cellular neutral lipids, but rather a complex and versatile organelle with diverse morphology, which has key roles in lipid metabolism, membrane traffic, protein degradation, and cellular signaling (Henne et al, 2019). The biological function of LDs is to provide ATP to the body by releasing free fatty acids (FFAs) and transporting them to mitochondria for β-oxidation during energy deprivation, fasting, and exercise (Figure 1; Welte and Gould, 2017;Santucci and Canaan, 2018;Dagpo et al, 2020). In mammalian adipocytes, changes in FIGURE 1 | Crosstalk in the metabolic machinery of LDs.…”
Section: Discovery Of Lipophagymentioning
confidence: 99%